Epidemiologia ambiental da esquistossomose em Alvorada de Minas, mesorregião metropolitana de Belo Horizonte, Minas Gerais: caracterização populacional de Biomphalaria (Gastropoda: Planorbidae), distribuição geográfica e observações sobre infecções naturais. - Paulo Ricardo Silva Coelho (2020)
Schistosomiasis, a parasitic disease caused by the trematode Schistosoma mansoni (Sambon, 1907) is endemic in Brazil and has in this environment the molluscs Biomphalaria glabrata (Say, 1818), B. tenagophila (d'Orbigny, 1835) and B. straminea (Dunker, 1848) as natural intermediate hosts. The municipality Alvorada de Minas is located about 210 km north of the capital of the state of Minas Gerais, on the tourist route of ‘Estrada Real’. The latest parasitological surveys pointed to the frequency of new cases of schistosomiasis in the population, which justifies carrying out studies aiming at determining potential sources of transmission. In the present study, five malacological surveys were made between October 2018 and September 2019. All collection points were georeferenced, environmentally characterized and the presence of faecal coliforms in the water was analyzed. The captured molluscs were individually evaluated, in the laboratory for the detection of possible infections by larvae of trematodes. The cercariae found were mounted on glass slides and identified in non-permanent preparations. Subsequently, the molluscs were identified taxonomically, based on morphological criteria and by molecular methods (PCR-RFLP) for species of the genus Biomphalaria. At the same time, for the confirmation of susceptibility, B. glabrata (F1 generation) from three locations and B. kuhniana was challenged with S. mansoni (strain LE) from UFMG. The data were georeferenced and represented on maps. Of 46 collection points, the presence of molluscs was confirmed in 16 of them, and specimens of the genus Biomphalaria were found in 13 field sites. Gastropods were found in rivers, brooks, lakes, ponds and drinking fountains for domestic animals. After screening, 1125 live mollusks belonging to the following genera and frequencies were found: Biomphalaria (68%), Physa (19,9%), Drepanotrema (5,8%), Omalonyx (3,9%), Pseudosuccinea (1,4%) and Pomacea (0,7%). By molecular analysis, the occurrence of B. glabrata, B. straminea, B. tenagophila, B. cousini (Paraense, 1966) and B. kuhniana (Clessin, 1883) was confirmed. Even though, all collected snails were negative for S. mansoni, other cercariae types were found in other gastropod species, such as: Xifidiocercaria, Strigiocercaria and Echinostoma-type larvae. Of the verified environments the examined field sites were characterized as 36% lotic environments and 64% lentic environments. The rapid assessment of habitat quality identified a greater presence of mollusks in the impacted environments and among the points with the presence of molluscs 72% presented faecal coliforms. Experimental infections of B. glabrata revealed a high susceptibility of the F1 generation of animals from the three locations evaluated, with an infection rate of 70%, 85% and 100%. B. kuhniana presented resistance to S. mansoni in laboratory infection. The making of maps made it possible to identify the distribution and grouping of limnic molluscs in the municipality and, consequently, to determine the possible areas of greater risk for transmission of schistosomiasis in Alvorada de Minas. Epidemiological care and intervention with control measures in the municipality should be prioritized in the eastern, central and northern regions, due to the increased risk of infection. This work can encourage the creation of more effective surveillance protocols, appropriate to the epidemiological profile of each endemic area, for the control of schistosomiasis mansoni